Protection of Intellectual Property Rights in the Perspective of Islamic Law - Erna Tri Rusmala Ratnawati; Rizqi Samera Al Farizi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
This article analyses the protection of intellectual property rights from the perspective of Islamic law. This article examines intellectual property rights by analyzing the concepts of wealth, rights, and ownership in Islamic law. This study employs a normative research method. The approach utilized in this research includes statutory and conceptual approaches. The data used in this study encompassed secondary data derived from primary, secondary, and tertiary legal materials. The research findings reveal that most scholars categorize intellectual property rights as a form of wealth, thereby subjecting it to similar treatment and legal consequences as other forms of wealth. Intellectual property rights constitute movable wealth, are permissible for utilization, lack a standardized market unit, and maintain their value even when exploited. Consequently, intellectual property can be transacted for profit and safeguarded by assessing its value when compensating for any loss. When acquired or discovered through means that adhere to Islamic law, intellectual property becomes a permissible right to possess. However, the ownership of these intellectual property rights under Islamic law remains constrained by Sharia principles.